Analisis Konsep Dan Penerapan Kesebangunan Dalam Pembelajaran Matematika: Studi Literatur Program Studi Pendidikan Guru Sekolah Dasar - Patricia Audy Justiana Simbolon; Dio Arta Yudha; Nurul Barkiah (CV. ITTC INDONESIA, 2026)
This study was carried out to examine the concept and implementation of similarity in mathematics learning through a literature review approach. The research applied a literature study method by reviewing various national and international scientific articles published between 2018 and 2025 obtained from Google Scholar, Scopus, and other academic sources. Data analysis was conducted through several stages, namely collecting, classifying, and interpreting findings from the selected literature. The findings reveal that the concept of similarity has an important contribution in improving students’ geometric thinking, spatial skills, and problem-solving abilities. In addition, the use of visual learning media and contextual teaching methods is considered effective in helping students understand proportional relationships in similar figures. Nevertheless, several studies show that students still face difficulties in identifying corresponding sides and angles in similar shapes. Therefore, more creative and interactive learning strategies are needed to strengthen students’ understanding of similarity concepts in mathematics education. This study is expected to become a reference and provide an overview of previous studies regarding the effectiveness of teaching similarity concepts in mathematics learning. The study also highlights the importance of collaborative activities and technology integration to support meaningful and effective mathematics instruction.